The Roles of Advertising and Product Quality on Online Customers' Satisfaction - Sukma, Pea (2011)
The daily growth of the internet and e commerce has changed the way of marketing and selling product and service. Internet is changing the way corporation conduct business with their consumers who are increasingly expecting higher service, becoming time saved, and wanting more convenience. The Internet has significantly increased the bargaining power of consumers and to sustain in this business field, business organization need to know how to satisfy their customer. The purpose of this research is to study the factor affected customer satisfaction towards online shopping among staff at University Utara Malaysia (UUM). The objectives of the study were 1) to determine which factor more contribute in online customer satisfaction among staff in UUM and 2) to examine the relationship between online customer satisfaction and quality of advertising, and product/service quality among staff in UUM. Data were collected from 60 from academic and non-academic staff by using simple random sampling where every each element in the population will have an equal chance of being included in the sample. Further, in this study data were analyzed using SPSS version 14.0 and the tests conducted were Pearson's Correlation and multiple regression. From the correlation and multiple regression analysis, the result indicates that the factor more contribute in online customer satisfaction is a quality of advertising compared with product/service quality factor. Besides, all the factor have a significantly and positive relationship towards customer satisfaction Recommendations for future research were also discussed.